The Emerging Role of Microbial Biofilm in Lyme Neuroborreliosis - Di Domenico, Enea Gino; Cavallo, Ilaria; Bordignon, Valentina; D'Agosto, Giovanna; Pontone, Martina; Trento, Elisabetta; Gallo, Maria Teresa; Prignano, Grazia; Pimpinelli, Fulvia; Toma, Luigi; Ensoli, Fabrizio (Frontiers in Neurology, 2018)
Lyme borreliosis (LB) is the most common tick-borne disease caused by the spirochete Borrelia burgdorferi in North America and Borrelia afzelii or Borrelia garinii in Europe and Asia, respectively. The infection affects multiple organ systems, including the skin, joints and the nervous system. Lyme neuroborreliosis (LNB) is the most dangerous manifestation of Lyme disease, occurring in 10-15% of infected individuals. During the course of the infection, bacteria migrate through the host tissues altering the coagulation and fibrinolysis pathways and the immune response, reaching the central nervous system (CNS) within 2 weeks after the bite of an infected tick. The early treatment with oral antimicrobials is effective in the majority of patients with LNB. Nevertheless, persistent forms of LNB are relatively common, despite targeted antibiotic therapy. It has been observed that the antibiotic resistance and the reoccurrence of Lyme disease are associated with biofilm-like aggregates in B. burgdorferi, B. afzelii and B. garinii, both in vitro and in vivo, allowing Borrelia spp. to resist to adverse environmental conditions. Indeed, the increased tolerance to antibiotics described in the persisting forms of Borrelia spp., is strongly reminiscent of biofilm growing bacteria, suggesting a possible role of biofilm aggregates in the development of the different manifestations of Lyme disease including LNB.